Overweight among seafarers working on board merchant ships - Giulio Nittari; Daniele Tomassoni; Marzio Di Canio; Enea Traini; Isabel Pirillo; Andrea Minciacchi; Francesco Amenta (BMC, 2019)
Abstract Background Obesity and overweight represent a relevant risk factor for seafarer's health. The frequency and distribution of overweight and obesity among seafarers working on board of Italian flag ships were studied. Analysis was made on occupational medicine files collected, in the frame of health surveillance inspections, between 2013 and 2016 from Centro Internazionale Radio Medico (CIRM). Methods The data of nationality, age, weight, height, blood glucose and blood pressure values obtained from 1155 seafarers were analyzed. Body mass index (BMI) values were calculated and compared with data reported for the general population of the same nationality of seafarers examined. Results BMI values revealed a tendency to overweight, whereas blood glucose and systolic blood pressure values were in general in the normal range. Approximtely 40% of subjects investigated were overweight, and more than the 10% of them were obese. Underweight was noticeable only in 1.22% of crew members and 0.34% of officers. The 0.52% of subjects investigated was diabetic, and 2.68% were hypertensive. Seafarers, regardless their nationality and rank, showed a greater tendency to overweight and obesity compared with general population of the same ethnicity. Conclusions Due to the occurrence of overweight and obesity among seafarers, campaigns for promoting awareness of the phenomenon and on the danger of these conditions for health should be promoted. Specific initiatives to avoid the assumption of junk food and the organization of adequate spaces, times and programs for physical exercise sessions on board should be offered for keeping seafarers healthier.